Chapter 15 The Politics of Tackling Inequalities The Rise of Psychological Fundamentalism in Public Health and Welfare Reform - Friedli, Lynne (Oxford University Press, 2015)
This chapter is concerned with the growing influence of non-material explanations for inequalities and a corresponding emphasis on psychological interventions, which aim to modify cognitive function or emotional disposition/affect (Friedli 2013, 2014). These developments intersect with and are reinforced by the parallel rise in brain science, which correlates a range of outcomes (crime, addiction, health behaviour, educational attainment) with brain structure (Katz 2013; Rose 2013).